Global marketing - Keegan, Warren J. (Pearson/Prentice Hall, 2005)
For undergraduate Global/International Marketing courses. Suitable at the MBA level if used with supplemental cases.Global Marketing, 4e, draws students into the excitement, challenges, and controversies of global marketing. Its paperback format gives adopters flexibility while ensuring the total cost to students is reasonable. The fourth edition is packed with new chapter opening vignettes, end-of-chapter cases (50% new!), and new coverage including more on global digital marketing (Ch 17) and CRM (Ch 6).